(untitled) (London Journal of Research In Humanities and Social Sciences, 2023)
According to the theory of human capital, one of the aspects that affects the growth of a country is the citizen’s capacity to work. This essay seeks to demonstrate a criticism of this theory and highlight education in the development of the human being and society Thus, through theoretical analysis, development is conceptualized from a holistic view and is related to topics of quality and equity. Finally, the importance of investment in education is sustained and it is concluded that an integral education is required to face the challenges of globalization.